Phytochemical Profile and Antioxidant Potential of Ethanolic Extracts from Ficus sur and Psidium guajava Leaves - Ogidi, Odangowei Inetiminebi; Christopher, Ejeomo; Orlu, Happiness Adaekwu; Alfred-Ugbenbo, Deghinmotei (Sciences of Phytochemistry, 2026)
This study evaluated the phytochemical profile and antioxidant activity of ethanolic leaf extracts of Ficus sur and Psidium guajava, two plants widely used in traditional medicine. Standard AOAC methods were employed for qualitative and quantitative phytochemical analyses. Antioxidant potential was assessed using DPPH, ferric reducing antioxidant power (FRAP), hydrogen peroxide (H₂O₂), and nitric oxide (NO) scavenging assays. Screening revealed that both species contained tannins, flavonoids, alkaloids, saponins, terpenoids, and steroids. Quantitatively, P. guajava outperformed F. sur in total phenolics (123.79 mg GAE/g), flavonoids (95.06 mg QE/g), and alkaloids (88.91 mg AE/g). However, at 1.0 mg/mL, F. sur demonstrated greater FRAP (2.19 µmol Fe²⁺/g) and DPPH scavenging (60.21%), while P. guajava exhibited superior H₂O₂ (61.18%) and NO (70.85%) scavenging activities. L-ascorbic acid showed the highest overall activity. In conclusion, both extracts possess significant antioxidant properties, supporting their traditional uses and highlighting their potential for pharmaceutical and nutraceutical formulations.